(3GdeQGLY GdGdcJQhfjI GdeJGMI Ydi GdGfJQfJ (B:s (3GdNUGFU hGdaFGJ, eYGjjQ GdJbjje, GdGOGQI hGdNOeI (B/s - (3GdfLGQ, eMeO eMehO QVG s ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2009)
(3jVe GdcJGH NeSI aUhd jHOC GhdG HGdJYQja ddeQGLY GdGdcJQhfjI GdeJGMI Ydi GdGfJQfJ h NUGFUgG Ke jJfGhd GdaUdGf GdKGfj h GdKGdK eYGjjQ GdJbjje GdeJYdbI HgPg GdeQGLY h cjajI JWHjbgG(B.. (3GeG aj GdaUd GdQGHY aJJVM dfG cjajI GOGQI gPg GdeQGLY Ke jMdd aj fgGjI GdcJGH (B-(3GdaUd GdNGeS(B- (3gPg GdNOeGJ GdeQLYjI GdGdcJQhfjI (B..(3eNJJeG HeUGOQ OQGSJg hbhGYO HjGfGJgGs
(3HHdjhZQGajG (B208- 224s
Keywords: (3GdGfJQfJ s; (3GdeQGLY GdGdcJQhfjI s; (3Yde GdecJHGJ s